Biokonversi Sampah Menggunakan Larva Black Soldier Fly - Yuliandari, Widyanti (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In the last hundred years, fly larvae have been used in organic waste treatment. House fly (Musca domestica L.) and Black Soldier Fly (Hermetia illucens L.) or BSF are two types of fly species that are often used in research for biodegradation of organic waste. This article aims to present  the utilization of BSF in organic solid waste treatment. This paper is based on a literature search of recent research on BSF.The advantage of utilizing BSF for bioconversion of organic waste is that its larvae grow with a high protein content and quickly, which has economic potential as animal feed. Two advantages of using BSF are high waste reduction efficiency and maximum prepupae biomass production. In this bioconversion process, there are factors that need to be considered, namely the type and composition of waste, moisture and toxic substances that affect the feeding rate. The economic potential of organic waste bioconversion using BSF is very high as evidenced by the data that one-third of food consumed by humans is wasted and becomes waste. BSF larvae grown from this food waste will produce fat- and protein-rich prepupae.